(untitled) (Journal of Nepal Geological Society, 2002)
The Kathmandu Valley lies in a synclinal basin filled up by fluvio-lacustrine sediments of Pleistocene age. Sundhara and Jamal lie at the core of Kathmandu City. The area is mostly occupied by public buildings. This paper primarily deals with distribution and engineering and geotechnical properties such as allowable bearing capacity of soil at Sundhara and Jamal area. For the purpose of identification of geotechnical properties of subsurface strata for multistoreyed buildings, data of borehole logging from fifteen drill holes and laboratory test of disturbed and undisturbed soil samples was used for the investigation. In the laboratory, index and mechanical properties such as grain size, natural moisture content, specific gravity, Atterberg limits, penetration resistance, cohesion, uniaxial compressive strength, angle of shearing, rate of consolidation, and settlement were evaluated. According to the National Building Code of India, the Kathmandu Valley is located in Seismic Zone V, and the recommended coefficient of horizontal acceleration for this zone is 0.08 g. Based on the present study of geotechnical properties of subsurface strata, it is recommended to increase the coefficient by up to 50 per cent for important structures. For multi-storeyed building, the tentative allowable bearing capacity for different types of foundation (strip, isolated. and raft) at different depths are determined as per the average parameters valid for the whole area.